(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
With the help of information technology, it is possible to quickly and accurately collect information about talented students. Information technology helps to identify the strengths and weaknesses of each student in the educational process. Through this, each student will be able to draw up an individual program, choose the most suitable methods for developing his talent. This article incorporates blockchain, cloud, machine learning, Artificial Intelligence and information technology. These technologies have been cited in detail in determining their talent requirements.